2010
DOI: 10.1159/000320049
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Novel Podocyte-Associated Proteins sult1b1 and ankrd25

Abstract: Background/Aims: Podocytes have a unique function in the renal ultrafiltration that is achieved by expressing proteins that are highly specific to podocytes. In this study, we identified two novel podocyte-associated proteins. Methods: The expression of sult1b1 and ankrd25 in mouse tissues was studied by RT-PCR. The protein expression was studied by generating polyclonal antibodies that were used in Western blotting and immunohistochemistry. Results: By RT-PCR we detected sult1b1 expression only in glomerular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Since WNK4 was present on both lists, a total of 5 genes were selected for analysis. Because the exact mouse ortholog for human KANK1 is unknown, because Kank2 is more highly expressed in mouse podocytes (49), and because Kank1 and Kank2 were recently identified as susceptibility genes for nephrotic syndrome, we targeted both Kank1 and Kank2. Multiple shRNAs were generated for the 6 candidate genes.…”
Section: Validation Of Wnk4 Kank1mentioning
confidence: 99%
“…Since WNK4 was present on both lists, a total of 5 genes were selected for analysis. Because the exact mouse ortholog for human KANK1 is unknown, because Kank2 is more highly expressed in mouse podocytes (49), and because Kank1 and Kank2 were recently identified as susceptibility genes for nephrotic syndrome, we targeted both Kank1 and Kank2. Multiple shRNAs were generated for the 6 candidate genes.…”
Section: Validation Of Wnk4 Kank1mentioning
confidence: 99%
“…In addition, this variant was absent from >6,500 controls (from 13,000 control chromosomes) in . For KANK2, a previous study showed that Kank2 mRNA is enriched in glomeruli rather than tubules in the mouse kidney and that KANK2 partially colocalizes with synaptopodin, but not with endothelial marker CD31, in human adult kidney (12). KANK2 localized to podocyte cell bodies as well as nuclei in rat glomeruli ( Figure 2B and Supplemental Figure 2B).…”
Section: Mutations In Kank2 Cause Ns In Humansmentioning
confidence: 78%